Familial Mediterranean fever associated with optic neuritis, successfully treated with anti-interleukin 1 agents - Başaran, Özge; Kavuncu, Sevim; Güven, Alev; Uncu, Nermin; Acar-Çelikel, Banu; Çakar, Nilgün (The Turkish Journal of Pediatrics, 2016)
Familial Mediterranean fever (FMF) is an inherited periodic auto-inflammatory disease characterized by recurrent attacks of fever, synovitis and serositis. Ophthalmological manifestations of FMF are extremely rare. Here we described a boy who has been followed-up for FMF and attended with a loss of vision during the course of the disease. He was diagnosed with optic neuritis. As the other etiologies were excluded his optic neuritis was attributed to the underlying auto inflammatory process. After pulse steroid therapy, his symptoms improved and a complete remission occurred. Afterwards he had two more optic neuritis attacks. Thereafter anti-interleukin 1 (IL-1) drugs were introduced and he did not develop further attacks of both optic neuritis and FMF. This case presentation highlights the possible association between FMF and optic nerve involvement.